Impoliteness Strategies Found in Deddy Corbuzier's Podcast on YouTube - Novalia, Agnes; Ambalegin, Ambalegin (e-Journal of Linguistics, 2021)
This study aimed at determining impoliteness strategies in a talk show entitled Deddy Corbuzier podcast on YouTube. In this research, the researchers used a theory from Culpeper (1996) . The researcher used qualitative method to analyse the impoliteness strategies in this study. This research used impoliteness strategies. The data source of the research was the talk show Deddy Corbuzier podcast on YouTube. This research contained utterances from the conversational dialogues in the talk show. Each utterance had several types of impoliteness strategies. In collecting data, this research used the non-participatory technique and observation method by Sudaryanto (2015) . Next, the data analyzed with the pragmatic identification method. This research found 15 data examined from the type of impoliteness strategy and the results were divided into bald on record impoliteness (5 data), positive impoliteness (4 data), negative impoliteness (3 data), mock politeness or sarcasm (2 data), withhold politeness (1 data). The most common strategy used by Deddy Corbuzier podcast on YouTube was bald on record impoliteness.